Identying Factors That Influences Fradulences in Non-Life Insurance Companies - Pathmananathan, P. Ravindran; Aseh, Khairi (Archives of Business Research, 2021)
Insurance fraud is the most common form of fraud in the world, aside from tax evasion. By its very existence, the insurance industry is prone to deception. Basic income levels in Vietnam have a tendency to steadily rise as a result of improving socioeconomic conditions. As a result, the need for citizen security has increased and become more diverse.The aim of this study is to study the predictor/s of anti-insurance fraud among non-insurer companies in Vietnam. This study was conducted using a questionnaire that was completed by 51 employees who are currently working in the 11 non-life insurance company in Vietnam. It can be concluded that there exists a significant relationship between all the four independent variables which are namely external regulations, public context, management functions as well as underwriting guidance.